ANALISIS PERLAKUAN AKUNTANSI AKTIVITAS AGRIKULTUR PADA PERUSAHAAN SEKTOR PERKEBUNAN YANG TERDAPTAR DI BEI MENJELANG PENERAPAN PSAK 69 - Hidayat, Muhammad (Universitas Riau Kepulauan, 2018)
This study aims to determine the implementation of PSAK 69 Agriculture (2015) on the financial statements of plantation industry companies in the period of 2017 in the year where it has been recommended early implementation before effective on January 1, 2018. Research sample consists of 8 (eight) registered plantation companies in Indonesia Stock Exchange 2017 obtained by using purposive sampling. This study uses descriptive comparative analysis that is by comparing statements that exist in PSAK 69 with its application in the financial statements.The results of this study indicate that 87.5% or 7 (seven) companies have not applied PSAK 69 Agiriculture, because the average level of application of PSAK 69 in the financial statements of these seven companies only reached 57%. Almost all of these plantation companies have not used the fair value method to measure the biological assets of their plantation crops in the 2017 financial statements. Keywords: PSAK 69, IAS 41, Biological Assets, Agricultural Products, Fair Value